2021
DOI: 10.3390/ijerph18030974
|View full text |Cite
|
Sign up to set email alerts
|

Navigational Needs and Preferences of Hospital Patients and Visitors: What Prospects for Smart Technologies?

Abstract: In this paper, we map navigational needs and preferences of patients and visitors to evaluate the appropriateness of a smartphone navigation application in the hospital in contrast to other, more traditional navigational cues. We test the effects of sociodemographic variables (age, gender, education) on wayfinding strategies and preferences of respondents (using chi2 tests). Empirical research is based on the survey among 928 patients/visitors of the Vítkovice Hospital in Ostrava, Czechia. We found a relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Wang et al ’s (2009) findings showed that gender has not statistically significantly affected attitudes toward mobile apps. Moreover, the findings of Ženka et al (2021) revealed no difference in attitudes toward mobile apps of Czech consumers by gender.…”
Section: Consumer Attitudes Toward Mobile Apps’ Designmentioning
confidence: 80%
“…Similarly, Wang et al ’s (2009) findings showed that gender has not statistically significantly affected attitudes toward mobile apps. Moreover, the findings of Ženka et al (2021) revealed no difference in attitudes toward mobile apps of Czech consumers by gender.…”
Section: Consumer Attitudes Toward Mobile Apps’ Designmentioning
confidence: 80%
“…People's age and gender influence their wayfinding strategies and behaviors ( Morag et al., 2016 ). One study shows that people over 60 years have a lower willingness to use mobile apps for navigation, and the need for improved navigation (including mobile apps) positively correlates with education level ( Ženka et al., 2021 ). People's educational background and knowledge structure also have an impact on wayfinding behaviors ( Morag et al., 2016, ), and different cultural backgrounds result in differences in the comprehension of the wayfinding visual aid such as healthcare symbols ( Joy Lo et al., 2016 ; S Lee et al., 2014 ; Wendy T. Olmstead, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to cope with the sequential nature of the medical treatment process, the spatial logical order of the public space of the hospital has been formed, and different spaces have been set up in different levels. Hospital public space is divided into a public center system, a public subsystem, and a connection system connecting the two according to the medical treatment process from high to low [9,10]. As shown in Figure 1, the logical order is arranged according to the relationship of reason, which conforms to the law of people's understanding of things.…”
Section: Main Characteristics Of Hospital Users' Pathfinding Behaviormentioning
confidence: 99%